Athens – An Incidental Democracy. A case of unintended consequences of institutional change - Carl Hampus Lyttkens (Lund University, School of Economics and Management, Department of Economics, 2004)
Around 600 B.C., Athens was ruled by a birth aristocracy. Some 150 years later, the city-state was a "democracy". A rational-actor perspective, as perceived in the new institutional economics, sheds additional light on this intriguing transformation by focussing our attention on the incentives of individual actors, for example. Furthermore, it illustrates the unpredictable nature of the long-run consequences of institutional change. Repeatedly, a result of the intra-elite competition for power was that members of the elite unwittingly contributed to the changes that eventually undermined their own dominant position as a group.
Keywords: D72; N43; 330; institutional change; unintended; democracy; Athens